Cumulative Lifestyle Profiles and Osteoporotic Fracture Risk in Older Women: A Nationwide Korean Cohort Study - Dojoon Park; Hae-Seok Koh; Seokwon Jeong; Ju-Yeong Park; Kyungdo Han; Youn-Ho Choi (Healthcare, 2026)
Background/Objectives: Modifiable lifestyle behaviors may be relevant to osteoporotic fracture risk, but their cumulative association across different levels of skeletal health remains unclear. This study investigated the association between a cumulative lifestyle score and osteoporotic fracture risk according to baseline bone mineral density (BMD) category in older women. Methods: We conducted a nationwide retrospective cohort study using Korean National Health Insurance Service data from 541,770 women aged 66 years who underwent dual-energy X-ray absorptiometry through the national life-transition health screening program between 2010 and 2016. A cumulative lifestyle score ranging from 0 to 3 was constructed by assigning one point each for regular exercise, non- or ex-smoking status, and non-drinking status. Cox proportional hazards models were used to evaluate associations with any, vertebral, hip, and other osteoporotic fractures across normal BMD, osteopenia, and osteoporosis groups. Results: Higher lifestyle scores were generally associated with lower osteoporotic fracture hazards across BMD categories. For any fracture, the adjusted hazard ratios for lifestyle score 3 versus 0 were 0.746 (95% CI, 0.564–0.987) in the normal BMD group, 0.747 (95% CI, 0.630–0.885) in the osteopenia group, and 0.786 (95% CI, 0.668–0.924) in the osteoporosis group. No statistical evidence of interaction between lifestyle score and BMD category was observed. The incidence-rate differences between scores 0 and 3 for any fracture were 4.49, 6.03, and 5.99 per 1000 person-years in the normal BMD, osteopenia, and osteoporosis groups, respectively. Conclusions: A more favorable cumulative lifestyle profile was associated with lower osteoporotic fracture risk across BMD categories in older women. Although there was no statistical evidence that the relative associations differed by BMD category, larger incidence-rate differences were observed among women with lower BMD. These observational findings support the potential value of integrated lifestyle assessment as a complementary component of fracture-risk assessment and counseling.